Una mirada al involucramiento paterno: participación de los hombres jefes de hogar de la Gran Área Metropolitana de Costa Rica en actividades de cuidado directo - Espinoza Herrera, Rebeca (El Colegio de México A.C., 2016)
As a result of the sexual division of labor, men and women have defined the roles, tasks and spaces they must assume in society: men are responsible for productive work and women for reproductive work. Although women have been incorporated into paid work, men do not participate in unpaid activities in the same way. This unequal distribution of housework and care activities is what led the author to analyze men’s participation in unpaid work, particularly the direct care of children under the age of 12. The article seeks to answer questions such as whether fathers and male heads of household in the Greater Metropolitan Area of Costa Rica with children under the age of 12 participate in direct care activities, what activities they are involved in and how much time they spend on them.